Protein Pool Maintenance During Oxidative Stress - Catalgol, B.; Grune, T. (Current Pharmaceutical Design, 2009)
The production of reactive species causes oxidative modifications of proteins accompanied by a loss of protein function. By protein oxidation all cellular compartments and any amino acid are effected. This might result in a defect of cellular homeostasis. Therefore, the degradation of non-functional, oxidized proteins is an essential function of the proteolytic branch of the antioxidant defense machinery. The major proteolytic system responsible for the removal of oxidized proteins is the proteasomal system. Whereas moderately oxidized proteins are more sensitive to proteolytic attack, severely oxidized ones are often poor substrates and might, however, inhibit the proteasome. This paper reviews the data available on protein modifications following oxidative stress, the cellular responses and the role of proteasome in this process.
Keywords: Reactive species